EVALUATION OF MECHANISMS AND DIFFERENTIAL DIAGNOSIS OF CLOSED DAMAGES OF INTERNAL ORGANS (BRAIN, LIVER, KIDNEY) UNDER THE ACTION OF PHYSICS - Козлов, Сергей; Козлова, Юлия; Корзаченко, Максим (SWorldJournal, 2021)
The paper considers scientific works devoted to the mechanisms and differential diagnosis of closed injuries of the brain, liver and kidneys due to blunt and explosion-induced injuries. Analysis of the literature has shown that the mechanism of developmen